2019
DOI: 10.3389/fphar.2019.01258
|View full text |Cite
|
Sign up to set email alerts
|

Positive Modulation of Angiotensin II Type 1 Receptor–Mediated Signaling by LVV–Hemorphin-7

Abstract: Hemorphins are hemoglobin β-chain–derived peptides initially known for their analgesic effects via binding to the opioid receptors belonging to the family of G protein–coupled receptor (GPCR), as well as their physiological action on blood pressure. However, their molecular mechanisms in the regulation of blood pressure are not fully understood. Studies have reported an antihypertensive action via the inhibition of the angiotensin-converting enzyme, a key enzyme in the renin–angiotensin system. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…A number of studies have highlighted their therapeutic potential [10,[17][18][19]47,48]. We had previously reported the molecular binding behavior of camel and non-camel LVV-hemorphin-7 on multiple targets [20,25]. Here, we report the binding and ACE inhibition potential of non-camel hemorphins (LVVYPWTQRF and YPWTQRF) and camel hemorphins (LVVYPWTRRF and YPWTRRF) using computational approaches and an in vitro ACE inhibition assay.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A number of studies have highlighted their therapeutic potential [10,[17][18][19]47,48]. We had previously reported the molecular binding behavior of camel and non-camel LVV-hemorphin-7 on multiple targets [20,25]. Here, we report the binding and ACE inhibition potential of non-camel hemorphins (LVVYPWTQRF and YPWTQRF) and camel hemorphins (LVVYPWTRRF and YPWTRRF) using computational approaches and an in vitro ACE inhibition assay.…”
Section: Discussionmentioning
confidence: 94%
“…It is also the most stable and has the highest hydrophobicity when compared to other hemorphins [15,16]. Numerous studies have reported various biological activities of hemorphins, such as effects on spatial learning, analgesia, and hypertension [10,[17][18][19][20]. Hemorphins have been shown to have beneficial effects in the control of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed a positive allosteric modulation of AT1R activity and signaling by LVV-H7 in HEK293 cells [ 14 ]. In this study, we examined the effect of LVV-H7 on the binding of AngII on AT1R using NanoBRET technology in real-time and intact cells as previously reported [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of ACE leads to reduced angiotensin II (AngII) levels, which are associated with the well-known anti-hypertensive properties of hemorphins [ 6 , 12 , 13 ]. Recently, we described for the first time the AngII type 1 receptor (AT1R) as a second GPCR to be pharmacologically targeted by the decapeptide LVV-hemorphin-7 (LVV-H7) in vitro with a positive modulation of its activity and downstream signaling pathways in HEK293 cells [ 14 ]. These effects were observed on the canonical Gαq/inositol phosphate pathway of AT1R, as well as on the phosphorylation of the extracellular signal-regulated-kinases (ERK1/2) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation